URGENSI KECERDASAN SPIRITUAL DAN EMOSIONAL GURU DALAM PENDIDIKAN KARAKTER SISWA DI SEKOLAH - M. I. Suhifatullah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Education in schools is not only an activity to develop aspects of students' intellectual intelligence, but also to develop various aspects of intelligence. This is in line with the Vision of the Ministry of National Education (now the Ministry of Education and Culture) 2025, namely